A Systematic Review of the Economic Burden of Diabetes in Eastern Mediterranean Region Countries - Arshad MS; Alqahtani F; Rasool MF (Diabetes, Metabolic Syndrome and Obesity, 2024)
Muhammad Subhan Arshad,1,2 Faleh Alqahtani,3 Muhammad Fawad Rasool1 1Department of Pharmacy Practice, Faculty of Pharmacy, Bahauddin Zakariya University, Multan, 60800, Pakistan; 2Department of Pharmacy, Southern Punjab Institute of Health Sciences, Multan, 60000, Pakistan; 3Department of Pharmacology and Toxicology, College of Pharmacy, King Saud University, Riyadh, 11451, Saudi ArabiaCorrespondence: Muhammad Fawad Rasool; Faleh Alqahtani, Email fawadrasool@bzu.edu.pk; afaleh@ksu.edu.saAbstract: Diabetes Mellitus (DM) is a highly prevalent non-communicable disease with high mortality and morbidity, which imposes a significant financial impact on individuals and the healthcare system. The identification of various cost components through cost of illness analysis could be helpful in health-care policymaking. The current systematic review aims to summarize the economic burden of DM in the Eastern Mediterranean Region (EMR) countries. The original studies published in the English language between January 2010 and June 2023 reported the cost of DM was identified by searching four different databases (Google Scholar, PubMed, Science Direct, and Cochrane Central). Two reviewers independently screened the search results and extracted the data according to a predefined format, whereas the third reviewer’s opinion was sought to resolve any discrepancies. The costs of DM reported in the included studies were converted to USD dates reported in the studies. After the systematic search and screening process, only 10 articles from EMR countries met the eligibility criteria to be included in the study. There are substantial variations in the reported costs of DM and the methodologies used in the included studies. The mean annual cost per patient of DM (both direct and indirect cost) ranged from 555.20 USD to 1707.40 USD. The average annual direct cost ranged from 155.8 USD to 5200 USD and indirect cost ranged from 93.65 USD to 864.8 USD per patient. The studies included in the review obtained a median score of 8.65 (6.5 ─ 11.5) on the quality assessment tool based on Alison’s checklist for evaluation of cost of illness studies. There is a significant economic burden associated with DM, which directly affects the patients and healthcare system. Future research should focus on refining cost estimation methodologies, improving the understanding of study findings, and making it easier to compare studies.Keywords: cost of illness, economic cost, healthcare cost, direct cost, indirect cost, diabetes